Linux Operating System Security Testing Case Study: FTP Security in Metasploitable2 - Hilmi, Muhammad Anis Al; Herdiyanti, Fauziah (SAINTEKBU, 2023)
Linux is an operating system like Unix that uses a kernel and includes applications and other support-ing modules to be used properly. Linux is free to use and includes open-source code to be used and devel-oped by all parties. The Linux operating system is widely used as a server, for example, for hosting web applications or used in cloud computing infrastructure. No wonder Linux is one of the targets of cyberat-tacks. In this study, a simulation of attacks on the Linux operating system was carried out, and one type of Linux distribution tested as a target was Metasploitable2. Metasploitable2 is a Linux operating system that is intentionally made vulnerable to attack; the aim is to be experimental material. In testing, Metasploitable2 was treated as the target of the attack and Kali Linux as the attacker. The initial stage of the attack simulation, carried out using NMap, Metasploitable2 security vulnerabilities can be identified and exploited for later attacks with exploits. The type of exploit used is a backdoor because a backdoor can function to penetrate systems, programs, or networks without going through the authentication pro-cess. In this case, Metasploitable2 has a security hole in its FTP port. The loophole is tried to be exploited. In this case, the way to overcome the attack is by closing all possible entry points to be an attack loop-hole; in this case, Metasploitable2 is port 6200 and disabling anonymous account permissions to upload files using FTP.